Examining the Effectiveness of Acceptance and Commitment Therapy (ACT) on Procrastination in Children with Stuttering Visiting Speech Therapy Centers in Tonekabon - Pezeshki Almani, Aram; Soghra Karbalai Herofteh, Fatemeh; Sanagouye Moharer, Gholamreza (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to examine the effectiveness of Acceptance and Commitment Therapy (ACT) on procrastination in children with stuttering who attended speech therapy centers in the city of Tonekabon. This research was a quasi-experimental study using a pretest-posttest design with a control group (with a two-month follow-up). In terms of purpose, the study was applied research. The statistical population included children with stuttering disorders visiting speech therapy centers in Tonekabon during the first half of 2021. A total of 30 children were randomly selected through purposive and convenience sampling (with three participants reserved as substitutes) and were assigned to either the experimental group or the control group (15 participants in each). The data collection tool was the Academic Procrastination Questionnaire developed by Solomon and Rothblum (1984). Data were analyzed using SPSS version 26, and the results indicated that the effects of time, group, and the interaction between time and group on procrastination were significant (p < .001). Based on the group effect and the mean scores table, ACT significantly reduced procrastination in children with stuttering in the experimental group compared to the control group. Furthermore, there was a significant difference across the assessment stages for each variable due to the time effect and the interaction between time and group. Therefore, it can be concluded that ACT is effective in reducing procrastination in children with stuttering who attend speech therapy centers in Tonekabon.